MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS - Lisa Syupriyanti; Taufina Taufina (Universitas Negeri Medan, 2020)
The purpose of this research was improve the students achievement in learning social science used PBL of 4th grade elementary school. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were students of 4th grade were 18 people consist of 8 men and 10 women. Research conducted in two cycles with research procedure includes of planning, implementation, observation, and reflection. The result of research was improve a) Lesson plan the cycles of I was 76,78% and the cycles II of 92,86% b) Implementation teacher’s activity of I cycle was 75% and II cycle was 92,86% while implementation students activity of I cycle was 73,22% and II cycle was 92,86% c) the students learning outcomes in the I cycle was 75,89 and II cycle was 86,82. It can be concluded that used PBL model can improve students achievement in learning social science of 4th grade at SDN 25 ATS Kota Padang.Keywords: Learning outcomes, Social science, PBL